Study on the Sustained Release and in vitro Efficacy Evaluation of Functionalized Carbon Nanotubes Chitosan Thermo-Sensitive Gel - Li, Xiaojuan; Guo, Yake; Chen, Wen (Asian Journal of Chemistry, 2014)
The purpose of this study was to synthesize a dual release of an amino-carbon nanotubes-chitosan thermo-sensitive gel. The chitosan/b-glycerophosphate (CS/b-GP) thermo-sensitive gel loaded with multi-walled carbon nanotubes/polyether imide (MWCNTs-PEI) was prepared by the simple solution casting method. The product was characterized by scanning electron microscopy and a fourier transform infrared spectrometer. Additionally, its toxic effect on PC12 cells was studied and the toxicity levels were evaluated. Nerve growth factor (NGF) was loaded by the CS/b-GP/MWCNTs-PEI gel. Its release property and biological activity were investigated using PC12 cells in culture media. The SEM and FTIR results showed that, after the MWCNTs-PEI were added, the pore size of the gel significantly decreased and its structure become more compact, which improved its sustained-release ability. The cumulative release of nerve growth factor decreased gradually as the added amount of MWCNTs-PEI increased and the cell differentiation rate reduced accordingly. The MTT experiments demonstrated that the relative growth rate of PC12 cells incubated with the thermo-sensitive gel ranged from 80.4-112 %, which reaches the biological material security evaluation criteria. The prepared gels displayed low toxicity as well as good sustained release ability, indicating they can be used as sustained release drug carrier. Keywords: Chitosan/